2017
DOI: 10.1016/j.jpeds.2016.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Enteral High Fat-Polyunsaturated Fatty Acid Blend Alters the Pathogen Composition of the Intestinal Microbiome in Premature Infants with an Enterostomy

Abstract: Objective To determine the effect of enteral fish oil and safflower oil supplementation on the intestinal microbiome in premature infants with an enterostomy. Study design Premature infants with an enterostomy were randomized to receive early enteral supplementation with a high fat-polyunsaturated fatty acid (HF-PUFA) blend of fish oil and safflower oil versus standard nutritional therapy. We used 16S rRNA gene sequencing for longitudinal profiling of the microbiome from the time of study entry until bowel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 41 publications
2
44
3
Order By: Relevance
“…Epidemiological investigations have determined that feeding mother’s own milk decreases the likelihood of necrotizing enterocolitis and late-onset sepsis in preterm infants [4,5,6], resulting in shorter hospital stays and decreased cost of care [7,8]. When mother’s own milk is not available, pasteurized donor milk (PDM) is used as a reasonable alternative for the preterm infant [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations have determined that feeding mother’s own milk decreases the likelihood of necrotizing enterocolitis and late-onset sepsis in preterm infants [4,5,6], resulting in shorter hospital stays and decreased cost of care [7,8]. When mother’s own milk is not available, pasteurized donor milk (PDM) is used as a reasonable alternative for the preterm infant [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For 16S rRNA sequencing, total genomic DNA was extracted from fecal samples using a commercial bead-beating method (Zymo Research Soil Microbe DNA kit, Irvine, CA). PCR amplification of the V4 region of the 16S rRNA gene and gel extraction of the PCR amplicons were performed as previously described (50). Sequencing was performed on the Illumina HiSeq Platform (Illumina, Inc., San Diego, CA) with the use of 150-nucleotide (nt) single-end reads.…”
mentioning
confidence: 99%
“…Sequencing was performed on the Illumina HiSeq Platform (Illumina, Inc., San Diego, CA) with the use of 150-nucleotide (nt) single-end reads. Sequences were filtered, clustered into operational taxonomic units (OTUs), and aligned to the Greengenes database (version 13.8.99) as previously described (50). Representative sequences of the clusters were assigned to a particular level of taxonomy using BLAST against the SILVA bacterial database (release 111).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies have found that dietary omega-3 fatty acid intake alters intestinal microbiota composition [31][32][33][34][35], and taxa increased in association with omega-3 fatty acid intake have been observed to include producers of SCFA [31][32][33]36]. In addition to potentially increasing SCFA production, PUFA can be metabolized by human gut microbes to produce metabolites including conjugated linoleic acids (CLA) [37,38].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%